Relationship between intangible resources, absorptive capacities and export performance - Alexandra França; Orlando Lima Rua (Tourism & Management Studies)
The new paradigm of today’s world economy is characterized by the mobility of production resources and the ability to combine them in an efficient way. The strategic management research has recognized the importance of studying the companies’ resources and capabilities and its usefulness to achieve competitive advantage. This perspective is consistent with the Resource-Based View (RBV) and with the Dynamic Capabilities View (DCV). The source of competitive advantage is much more correlated with intangible resources, since these are rarer and socially complex, making their imitation difficult. Consequently, intangible resources are considered strategic resources, since it allows creating perceived value by the customer, outperforming the competition, competing in new markets and being use in a wide range of products and services. On the other hand, the processes for absorbing external knowledge became an essential element for firms to adapt to changes in the competitive environment. Thus knowledge plays an important role in firms’ internationalization process. Building on well-established theories, our research explores the influence of intangible resources and absorptive capacities in export performance of Portuguese small and medium enterprises (SMEs) of footwear associated to the Portuguese Footwear, Components and Leather Goods Association (APICCAPS). Based on survey data from 42 firms, our empirical results indicate that globally intangible resources and absorptive capacity have a positive and significant influence on export performance. On one hand, the intangible resources that most contribute to this end are reputational resources, access to financial resources and relational resources, and on the other hand the absorptive capacities that most contribute to export performance are exploitation of knowledge, transformation of knowledge and general knowledge acquisition.